Draft genome sequence data of Antarctic Penicillium sp. strain E22, from Deception Island - Teoh Chui Peng; Paris Lavin; Rómulo Oses Pedraza; Natalia Fierro-Vásquez; Cristina Purcarea; Sheau Ting Yong; Clemente Michael Wong Vui Ling (Elsevier Inc., 2024)
Here, we report the draft genome sequence and assembly of the Penicillium sp. strain E22, which was isolated from Antarctic soil of Deception Island, South Shetland Islands close to the Antarctic Peninsula. The genome was sequenced using a 2 # 250 bp paired-end method by Illumina MiSeq 6000. The genome assembly was performed using softwares implemented in the Kbase web service. The phylogenetic tree of strain E22 comparing its internal transcribed spacer (ITS) region with the other Penicillium showed high genetic similarity to Penicillium griseofulvum MN545450 and Penicillium camemberti MT530220. Draf genome of Penicillium sp. strain E22 comprises 33,653 coding sequences, with a high G + C content of 48.32% and a total size of 37,484,944 bp. This draft genome assembly version has been deposited at GenBank under accession JASJUN000000000.